SECURITY ENCAPSULATING PAYLOAD IP SECURITY PROTOCOL IN AS - Marzuki Marzuki Marzuki (Majalah SIKOMTEK, 2006)
Today's world of information about crime on the Internet computer network, such as attacks,especially viruses, worms, Trojans, Denial of Service (DoS), Web defacement, hijackingsoftware, up to the problem of theft of credit card more often adorned the pages of massmedia. Crime in the world of computers continues to increase in line with the developmentand advancement of science and technologies in this field. This challenge is actually alreadyappeared since the beginning. Encapsulating security payload (ESP) is a protocol used inInternet Protocol Security (IPSec) and in addition the Authentication Header (AH) is anotherprotocol which is a service that provides confidentiality, and authentication.In this article will discuss about the encapsulating protocol IPsec Security as a service.